(untitled) (Bangladesh Pharmaceutical Journal, 2023)
Rourea minor is a species which belongs to the family Connaraceae. Rourea minor reported previously for antibiotic, antibacterial, hemostatic and wound-healing activities. In this study, we evaluated the antioxidant, thrombolytic and membrane stabilizing activities of the crude methanolic extract of the leaves of Rourea minor and its different organic soluble fractions. We measured the total phenolic contents and 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity of the extracts to observe their antioxidant potential. The thrombolytic activity was determined by human blood clot lysis. Anti-inflammatory activity was evaluated by human red blood cell (HRBC) membrane stabilization based on hypotonic solution- and heat-induced haemolysis. The total phenolic content ranged from 9.4 to 57.4 mg GAE/g of the dry extracts and IC50 values of the different extracts (Crude methanol, petroleum ether, ethyl acetate and aqueous) were between 20.38 and 269.34 μg/ml. All the extracts showed mild to moderate thrombolytic potential inhibiting the lysis of clot by 3.47% - 18.43%. The extracts also exhibited potential membrane stabilizing activity in both hypotonic solution- and heatinduced haemolysis indicating their anti-inflammatory activity. Thus, it can be concluded that the methanolic extract from the leaves of Rourea minor and its different fractions possess mild to moderate antioxidant, thrombolytic activities, and membrane stabilizing potential. Bangladesh Pharmaceutical Journal 26(1): 51-55, 2023 (January)